Public perceptions of urban forests in Ibadan, Nigeria: Implications for environmental conservation (2001)
This work examines the public perceptions of urban forests in Ibadan vis- a-vis environmental conservation. It covers the five Local Government Areas (LGAs): lbadan North, Ibadan North West, Ibadan South, Ibadan South-West, and Ibadan South-East. Data for the study was obtained from a stratified random sampling of 370 respondents through structured questionnaire-based interviews. The results showed that 99 per cent of the respondents are aware of, and believe that these urban forests serve some purpose in meeting the socioeconomic and physiological needs of the urban populace. Moreover 94 per cent expressed their support for continued preservation of these forests. Of this total, 38 per cent, 36 per cent and 26 per cent respectively, based their support on the fact that these forests can: protect the environment, supply physical needs and be used for recreation. The chi-square test of independence at P = 0.05 revealed that the public perceptions of these forests are dependent on the respondents' residence proximity to at least one of these forest reserves (P > 0.05). Public perceptions may be capitalized upon by governments and other change agencies for the sustainable management of the remnants of Ibadan urban forests.